Analisis Penerapan Asas Rahasia dalam Pelaksanaan Pemilihan Umum Berdasarkan Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum - Malviani, Silvi; Nuriman, Nuriman; Rosidin, Utang (SIYASI: Jurnal Trias Politica, 2025)
The secrecy principle in elections is enshrined in Law Number 7 of 2017 and other related regulations. However, in practice, its application is only enforced within the voting booth. Moreover, various external factors, such as advances in information technology and the presence of quick-count survey institutions, have contributed to the erosion of the secrecy principle in elections. This study aims to provide recommendations to legislative bodies and raise public awareness of the need to uphold the secrecy principle from the beginning of the election process through to its conclusion. The research adopts a normative juridical method, requiring the collection of both primary and secondary data, followed by an analytical process. Three theories are used: the theory of legal purpose, the theory of legislative hierarchy, and the theory of democracy. This article concludes that the secrecy principle as stated in Law Number 7 of 2017 is no longer relevant, emphasizing the need for legal reform to better align with Indonesia’s evolving dynamics.